1993
DOI: 10.1063/1.1144475
|View full text |Cite
|
Sign up to set email alerts
|

An electrostatic levitator for high-temperature containerless materials processing in 1-g

Abstract: This article discusses recent developments in high-temperature electrostatic levitation technology for containerless processing of metals and alloys. Presented is the first demonstration of an electrostatic levitation technology which can levitate metals and alloys (2-4 mm diam spheres) in vacuum and of superheating-undercooling-recalescence cycles which can be repeated while maintaining good positioning stability. The electrostatic levitator (ESL) has several important advantages over the electromagnetic levi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
175
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 332 publications
(181 citation statements)
references
References 9 publications
0
175
0
1
Order By: Relevance
“…Other details about the HTESL are given in an earlier publication. 7 To excite the drop oscillations a few modifications had to be made to the existing electrostatic levitator. These included the insertion of an ac voltage amplifier between the bottom electrode and the electric ground as schematically shown in Fig.…”
Section: Experimental Arrangement and Proceduresmentioning
confidence: 99%
“…Other details about the HTESL are given in an earlier publication. 7 To excite the drop oscillations a few modifications had to be made to the existing electrostatic levitator. These included the insertion of an ac voltage amplifier between the bottom electrode and the electric ground as schematically shown in Fig.…”
Section: Experimental Arrangement and Proceduresmentioning
confidence: 99%
“…6,7 The sample temperature was measured using an E 2 T pyrometer ͑model 7000ET-1HR͒. Prior to the temperature measurements, the pyrometer was calibrated using the known eutectic temperature of 937 K. Initially, the molten sample was cooled radiatively to a predetermined temperature by blocking the heating source of a xenon arc lamp.…”
mentioning
confidence: 99%
“…This lends the material to experimental study of its undercooling and solidification behavior. The containerless high-temperature high-vacuum electrostatic levitation ͑HTHVESL͒ processing technique 6 permits comprehensive studies of thermophysical properties in deeply undercooled liquid metals. By applying the HVHTESL technique to the Zr 41.2 Ti 13.8 Cu 12.5 Ni 10.0 Be 22.5 alloy, for example, the authors found that proper thermal treatment during solification results in the ''self-fluxing'' of the melt, allowing it to successfully undercool down to the glass transition with cooling rates of about 1 K/s.…”
mentioning
confidence: 99%
“…Modest cooling rates of 10 3 K/s or less have been applied to attain deep undercoolings in many binary and ternary alloys such as Pd-Si, 2 Pd-Cu-Si, 3 Au-Pb-Sb, 4 and Pd-Ni-P. 3,5 Very slow cooling rates ͑0.3 K/s or less͒ have resulted in sufficiently large undercooling to form glassy Te-Cu alloys in the form of a fine droplet emulsion. 6 To achieve a deeply undercooled liquid state, high-temperature high-vacuum electrostatic levitation 7 has been developed as a containerless process which eliminates the need for a melt containment vessel that often initiates heterogeneous nucleation. Recently, the undercooled melt of a Zr-Ti-Cu-Ni-Be alloy has been found to exhibit extremely high thermal stability.…”
mentioning
confidence: 99%